Ternary lanthanide complexes of the type M(HSal)3(TBP)2: Preparation and spectroscopic studies - Sinha, Shyama P. (Elsevier, 1971)
Ternary lanthanide complexes of the general formula M(Hsal)3(TBP)2, where M(III) = lanthanide or yttrium ion, Hsal = salicylate ion = C6H4(OH)COO- and TBP = tri-n-butylphosphate, have been prepared by a liquid-liquid extraction method. The coordinated nature of the salicylate ion and TBP has been established from the studies of the i.r. spectra of the complexes. The electronic spectra of the ternary Pr, Nd, Sm, Dy, Er and Yb complexes showed the expected enhancement of intensities for the hypersensitive bands. However, except in the case of Nd(III)-complex, where a minute red shift has been observed, other complexes do not show the expected nephelauxetic shift. © 1971.